Analysis of circular RNA expression profiles of lung cancer in Xuanwei, China. Issue 12 (26th August 2020) - Wang, Yan; Lu, Ling‐Jiao; Duan, Yong; Liu, Xiao; Mao, Yue; Chen, Yu; Zhang, Yan‐Liang
Abstract: Background: Mounting evidence indicates that circular RNAs (circRNAs) could play a pivotal role in cancers. However, due to the lack of sensitive biomarkers, most lung cancer in Xuanwei (LCXW) patients are still diagnosed at an advanced stage accompany with distant metastasis. Methods: According to the stage of LCXW patients and tissue sources, circRNAs microarray detection was carried out in six groups. Considering fold change, raw intensity, the length of circRNAs, and P‐ value, we selected eight circRNAs for further study. A total of 50 paired LCXW tissues were carried out real‐time quantitative polymerase chain reaction (RT‐qPCR) in order to extended sample size to verify the expression of these circRNAs. Results: We designed 13 617 human circRNA probes for the human circular RNA microarray, detected 10 819 circRNA in six groups of samples; 537 circRNAs were differentially expressed consistently in every stage. Through RT‐qPCR, we selected 8 circRNAs, three of which were upregulated (hsa_circ_0005927, hsa_circ_0069397 and hsa_circ_0000937) and five were downregulated (hsa_circ_0001936, hsa_circ_0005255, hsa_circRNA_406010, hsa_circ_0007064, hsa_circ_0000907) in tumor tissues, only hsa_circ_0001936 showed the opposite expression between microarray and RT‐qPCR, others were consistent. Additionally, hsa_circ_0005927 and hsa_circ_0001936 were significantly correlated with tumor size, and hsa_circRNA_406010 was related to the prognosis of LCXW patients. Conclusion: Together, these results suggest that hsa_circ_0005927, hsa_circ_0001936, and hsa_circRNA_406010 may serve as the novel potential biomarkers for LCXW. Moreover, these results may provide a new insight for the pathogenesis of LCXW. Abstract : A‐D, The relative expression levels of hsa_circRNA_104600, hsa_circRNA_069397, hsa_circRNA_105013, and hsa_circRNA_406010 were examined in 50 paired tissue samples by RT‐qPCR; (E) Comparison of circRNA expression levels between RT‐qPCR results and microarray. Candidate circRNAs of differential expression in microarray were validated by RT‐qPCR in LCXW samples. The heights of the columns represent the mean fold changes of expression level between LCXW and normal group. Asterisks indicate significant differences (* means P  ≤ .05; **means P  ≤ .01; *** means P  ≤ .005; **** means P  ≤ .001). (F) The relative expression levels of mRNA HECW2 were examined in 37 paired tissue samples by RT‐qPCR; mRNA HECW2 was significantly downregulated in LCXW tissues. (G) The relative expression levels of mRNA HECW2 and hsa_circRNA_406010 in 37 paired LCXW samples have no correlation.